2020
DOI: 10.5539/gjhs.v12n9p129
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia Infant and Young Child Feeding Practice: The Role of Women’s Empowerment in Household Domain

Abstract: Previous studies showed the significant association between women’s empowerment and infant and young child feeding (IYCF) practice. Only around 40% of Indonesian children met adequate IYCF practice. Hence, each dimension of women’s empowerment in the household domain must be explored. We carried out a dataset of the 2017 Indonesia Demographic and Health Survey, with samples of 4,880 mothers of reproductive age in a marriage relationship with their last-born child aged 6-23 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
(57 reference statements)
0
12
0
1
Order By: Relevance
“…Karakteristik sosial demografi dan ekonomi rumah tangga akan memengaruhi capaian MAD. Berbagai studi di Indonesia maupun beberapa negara lainnya menunjukkan bahwa aspek perekonomian rumah tangga yang diukur melalui indeks kekayaan akan memengaruhi MAD (Akalu et al, 2021;Bappenas RI, 2018;Puspitasari & Gayatri, 2020;Zebadia et al, 2021a). Oleh karena itu, adanya keberadaan penduduk miskin dapat berpengaruh terhadap penurunan pendapatan dan daya beli pangan sehingga berdampak pada kuantitas dan kualitas konsumsi pangan rumah tangga yang memiliki anak usia 6-23 bulan.…”
Section: Pendahuluanunclassified
“…Karakteristik sosial demografi dan ekonomi rumah tangga akan memengaruhi capaian MAD. Berbagai studi di Indonesia maupun beberapa negara lainnya menunjukkan bahwa aspek perekonomian rumah tangga yang diukur melalui indeks kekayaan akan memengaruhi MAD (Akalu et al, 2021;Bappenas RI, 2018;Puspitasari & Gayatri, 2020;Zebadia et al, 2021a). Oleh karena itu, adanya keberadaan penduduk miskin dapat berpengaruh terhadap penurunan pendapatan dan daya beli pangan sehingga berdampak pada kuantitas dan kualitas konsumsi pangan rumah tangga yang memiliki anak usia 6-23 bulan.…”
Section: Pendahuluanunclassified
“…10, 17 Our study also shows a consistence result with previous study in Indonesia using 6-23 months population showing a significant association between wealth index and MDD. 9 Children who lived in the higher wealth index quintile had better privilege to have more diverse foods due to wider food options and bigger buying power of the family. Access to internet was increasingly used as the proxy indicator to describe access to information.…”
Section: Original Articlementioning
confidence: 99%
“…The result of the study shows that wealth index, number of children, assets ownership, mother's working status, and place of residence were associated with MDD. 9 Previous study in Tanzania shows that children in younger age (6-11 months old), limited access to media, and poor economic status were associated with inappropriate feeding practice. 10 Better understanding on determinants of MDD among 6-11 months is needed to increase MDD practices and to prevent malnutrition.…”
Section: Introductionmentioning
confidence: 97%
“…Infant nutrition is essential for children's health and development during childhood and also during adolescence and adulthood [9]. Prior to the age of two, optimal breastfeeding and sufficient supplementary feeding habits for infants and young children are also protective factors against stunting and wasting [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 25.9% of children did not eat more than 3-4 types of complementary foods (breast milk, formula, cheese/yogurt, or other dairy products), 44.5% of children did not eat according to the minimum frequency according to their age, and 57.7% of children aged 6-23 months did not receive all three variations of these infant and young child feeding (IYCF) practices. Suboptimal feeding practices and a high prevalence of underweight, wasting, and stunting were found among children aged 6-23 months [11,13]. A study in Aceh showed that of 39% of children aged 6-23 months who received exclusive breastfeeding, only 61% received long-term breastfeeding, and 50% received timely complementary feeding.…”
Section: Introductionmentioning
confidence: 99%